Amylose, rheological and functional properties of yellow cassava flour as affected by pretreatment and drying methods - Ekeledo, E.; Latif, S.; Abass, A.; Muller, J. (Elsevier, 2023)
This study reconnoitered the effects of preservative treatments (0.3% Sodium Metabisulphite solution (SMS); and 0.3% Citric Acid solution (CAS)) and drying methods (flash- and cabinet-drying) on the rheological profile, amylose and functional properties of flour from yellow-fleshed cassava varieties. Four preservative-treated flour samples (Sodium Metabisulphite cabinet-dried (SMC); Sodium Metabisulphite flash-dried (SMF); Citric Acid cabinet-dried (CAC); and Citric Acid flash-dried (CAF) were evaluated. The rheological profile (peak, breakdown, setback and final viscosity) of flash-dried samples treated with sodium metabisulphite exhibited the highest values (891 RVU, 586 RVU, 208 RVU and 513 RVU) respectively. The cabinet-dried samples treated with citric acid had the least peak, trough and final viscosity of 497 RVU, 211 RVU and 326 RVU respectively. The flash-dried flour samples had the highest values for water absorption capacity while cabinet-dried (CAC) flour samples had the highest dispersibility. Therefore, flash-dried flour samples are more likely suited for food formulations requiring good pasting quality and moderately high gel strength.